2022
DOI: 10.1017/s2040174422000150
|View full text |Cite
|
Sign up to set email alerts
|

Twins in Guinea-Bissau have a ‘thin-fat’ body composition compared to singletons

Abstract: The ‘thrifty phenotype’ hypothesis proposed that fetal undernutrition increases risk of diabetes in later life. Undernourished low birthweight Indian babies are paradoxically more adipose compared to well-nourished European babies, and are at higher risk of diabetes in later life. Twin pregnancies are an example of in utero growth restrictive environment due to shared maternal nutrition. There are few studies of body composition in twins. We performed secondary analysis of anthropometric body composition of tw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…However, the central fat measures used in this study provide a combined measure of subcutaneous and visceral fat, and thus further exploratory work is required [ 55 ]. Previous studies have indicated that childhood skinfold thicknesses and circumferences can serve as proxy indicators of lipid and insulin dysregulation, and that differences in fat deposition, as reflected by BMI, circumferences and fat free mass, can be used to assess cardiometabolic risk [ 28 , 41 , 56 ]. This may indicate higher cardiometabolic risk in First Nations children even from early childhood, consistent with studies from other populations describing the ‘thin-fat’ phenotype [ 41 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the central fat measures used in this study provide a combined measure of subcutaneous and visceral fat, and thus further exploratory work is required [ 55 ]. Previous studies have indicated that childhood skinfold thicknesses and circumferences can serve as proxy indicators of lipid and insulin dysregulation, and that differences in fat deposition, as reflected by BMI, circumferences and fat free mass, can be used to assess cardiometabolic risk [ 28 , 41 , 56 ]. This may indicate higher cardiometabolic risk in First Nations children even from early childhood, consistent with studies from other populations describing the ‘thin-fat’ phenotype [ 41 , 43 ].…”
Section: Discussionmentioning
confidence: 99%